Meningkatkan Kesadaran Pemuda/I HKBP Rogate Medan Tentang Penyalahgunaan Media Sosial Sebagai Modus Human Trafficking - Hia, Niscaya; Sarah, Eva Margareth; Marpaung, Rolando; Laia, Exmin Jaya; Marbun, Atiek S. (Universitas katolik Musi Charitas, 2024)
Many young people are not aware of the mode of Human trafficking so that many become victims, especially through social media. The current generation of youth is very different from the previous generation in terms of socializing, how to think, and how to solve problems. Many teenagers also abuse social media such as spreading hoax news, defamation and other crimes. This counseling activity is one way to build legal awareness to youth by providing information to be wise in using social media and can avoid the practice of Human trafficking where they will become the next generation in the future. The method used in the implementation of this counseling activity is adjusted to the problems of the partners and the solutions provided from the counseling activities. The approach method is related to providing understanding to PbM-KT participants on the threat and prevention of human trafficking. The results obtained through this counseling activity are youth in the HKBP Rogate Medan Church environment understand the dangers of Human trafficking practices, understand the laws related to Human trafficking and how to be wise in social media so as to avoid the practice of human trafficking.